2002
DOI: 10.1080/mmy.40.3.311.313
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the hospital environment on yeast colonization in nursing students

Abstract: Fungemias have increased in recent decades, with high indices of morbidity and mortality. The agents of fungal infection isolated most often are yeasts, which can be acquired by direct contact with already colonized individuals. The present study aimed to detect yeast colonization in nursing students, and to study the possible influence of the hospital environment on colonization. The nasal cavities and hands of 22 students were sampled before and after a 62-day hospital training period. The yeast colonies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
2
5
0
5
Order By: Relevance
“…Author observed fungi in 48% of surveyed students in the autumn, and in 46% in the spring. The prevalence of fungi in students of Medical Sciences was similar to that recorded by Bonassoli and Svidzinski [21] in nursing students. Of the 22 students examined, as many as 15 were found to be colonized by yeasts, 68%.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Author observed fungi in 48% of surveyed students in the autumn, and in 46% in the spring. The prevalence of fungi in students of Medical Sciences was similar to that recorded by Bonassoli and Svidzinski [21] in nursing students. Of the 22 students examined, as many as 15 were found to be colonized by yeasts, 68%.…”
Section: Discussionsupporting
confidence: 66%
“…In a study conducted by Majima et al [22] among dental students was found a significantly lower prevalence of fungi in the oral cavity, at 18.7%. Bonassoli and Svidzinski [21] suggest that the high prevalence of fungi in subjects related to health care, among others nurses, physicians and medical students, can promote the spread and occurrence of fungal infections among patients, especially with impaired immune system function. Previous studies indicate that this relationship may be mutual, that is, the hospital environment can be a source of infection for staff and apprentices/trainees, evidenced by the fact that a much higher prevalence of fungi, but with less diversity, were found among FMS students than FB&B students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recentemente, a repetição de tandens curtos (STRs) ou microssatélites, também têm assumido um papel importante como marcadores moleculares de genomas eucariotos em diversas áreas, como na oncogenética, genética de populações e na caracterização e identificação de isolados (SAMPAIO et al, 2003). Estes ocorrem em milhares de cópias dispersas em todo o genoma, são geralmente constituídos por 1-6 nucleotídeos e exibem alto polimorfismo, transmissão codominante Mendeliana e tipagem por PCR (BOTTEREL et al, 2001). Alguns poucos lócus de microsatélites polimórficos tem sido identificados em relação ao genona de C. albicans, estando a maioria deles localizados próximos ou no interior de regiões codificadas e, exibindo um poder discriminatório entre 0.77 e 0.91 (LUNEL et al, 1998;METZGAR et al, 1998).…”
unclassified
“…Os microssatélites são considerados marcadores estáveis, de fácil análise, adaptável à séries de ampla escala e com grande poder discriminatório, sendo utilizado como sistema de tipagem para investigar problemas clínicos, tais como a transmissão nosocomial de C. albicans (BOTTEREL et al, 2001).…”
unclassified